MULTIPLE SENSOR MEASUREMENT SYSTEM USING RASPBERRY PI PICO MICROCONTROLLERS - CHYHIN, VASYL; FROLOVA, ANASTASIIA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
There were investigated alternative methods for receiving and analyzing multiple signals from different sources, and conducted a literature review in relevant areas. In particular, we analyzed an expansion board of the ReSpeaker 6-Mic Circular Array Kit type based on a Raspberry Pi minicomputer, which is equipped with six microphones and is intended for applications in the field of artificial intelligence and voice interfaces. It is shown that the ReSpeaker board has limited application, it is intended for stationary use with limited scalability. In this work, the authors created and tested an experimental electronic system for processing signals from twelve sensors using four Raspberry Pi Pico microcontrollers, as well as software compiled using the micropython language, which allows us to significantly expand the scope of its application. Condenser microphones complete with amplifiers of the KY-037 module type were used as highly sensitive sensors. The conversion of an analog signal into a digital one and its primary processing is carried out using Pico microcontrollers for the implementation of high-precision embedded systems. To ensure data exchange between microcontrollers and the central node and peripheral devices, a one-way I2C serial bus was used, which provides synchronous, multi-controller network communication. Its use is associated with setting a short distance between the boards, on the order of tens of centimeters. The main functions of microcontrollers are analog-to-digital conversion of signals at the output of amplifiers, calculation of the average intensity of signals from each microphone, comparison of averaged signals to detect the maximum intensity, formation and transmission of data to a buffer or central node. The effectiveness of the experimental system was checked using compiled software tools that provide real-time processing of sound signals. Thanks to the successfully selected hardware and software components, a prototype of the system was created, capable of operating effectively in field conditions.